ChemInform Abstract: Functionalized Ionic Liquids for the Synthesis of Metal Nanoparticles and Their Application in Catalysis. Issue 1 (3rd January 2013) - Luska, Kylie L.; Moores, Audrey
Abstract Review: ca. 100 refs.